Poliquistosis en pacientes que acuden a consulta externa de ginecología en el Hospital Manuel Ygnacio Monteros Valdivieso - Loja. - Alejandro Montalván, Daniel Efraín (2016)
This thesis work entitled “Polycystic ovary disease in patients who attend the Gynecology outpatient services clinic of the Manuel Ygnacio Monteros Valdivieso Hospital – Loja”, aimed to determine the prevalence of polycystic ovary disease, define the most common age range in which it occurs and determine the associated risk factors of patients diagnosed with Polycystic Ovary Syndrome. This is a cross-sectional descriptive study. A data collection sheet was used and the obtained results were taken from the AS400 system, which is a tool used by IESS to fulfill their daily duties. In our society it was determined that Polycystic Ovary Syndrome has a prevalence of 2.2% and the most affected age range was between 15 and 25 years old. The majority of these patients were overweight with 45.83%, with regard to Blood Pressure it was found that the 12.5% of the patients presented HTA, while 16.67% had Diabetes, and 65,22% of patients presented infertility and abortion problems. Keywords: polycystic ovary syndrome, prevalence, age range, risk factors.